Response to ovulation trigger is correlated to late follicular phase progesterone levels: A hypothesis explaining reduced reproductive outcomes caused by increased late follicular progesterone rise. Issue 5 (30th March 2019) - Friis Wang, N; Skouby, S O; Humaidan, P; Andersen, C Y
Abstract: STUDY QUESTION: Is there an association between progesterone (P4 ) levels on the day of hCG or GnRH trigger and on the day of oocyte retrieval in IVF/ICSI cycles? SUMMARY ANSWER: A significant positive correlation between P4 levels on the day of trigger and the day of oocyte retrieval is seen; HCG trigger induces a steeper P4 increase than GnRHa trigger. WHAT IS KNOWN ALREADY: FSH induces LH receptor (LHR) expression on granulosa cells, and LHR produces progesterone when exposed to LH-like activity. FSH per se also to some extent induces P4 secretion. Late follicular phase progesterone rise has been associated with reduced reproductive outcomes. STUDY DESIGN, SIZE, DURATION: This study is based on data from a previously published RCT conducted from 2009 to 2011. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 384 participants were enrolled; 199 received 5000 IU hCG and 185 received buserelin 0.5 mg for triggering ovulation. P4 was measured on the day of ovulation induction and on the day of oocyte retrieval. FSH consumption and number of retrieved follicles were recorded. MAIN RESULTS AND THE ROLE OF CHANCE: A significant linear relationship between P4 on the day of ovulation induction and oocyte retrieval was seen in the hCG trigger group ( P < 0.00001) as well as in the GnRHa trigger group ( P < 0.00001). The P4 ratio (the increase in P4 between ovulation induction and oocyte retrieval) was significantly higher in the group of patients with <5 follicles compared to those with 5–15 and >15 follicles ( P < 0.0001). The FSH consumption per follicle was significantly higher in the group of patients with <5 follicles compared to those with 5–15 and >15 follicles ( P < 0.0001). LIMITATIONS, REASONS FOR CAUTION: Although the study demonstrates a significant correlation between P4 levels before and after ovulation trigger, it does not demonstrate a causal relation to the number of LHRs present on granulosa cells. WIDER IMPLICATIONS OF THE FINDINGS: The findings of this study support the proposed hypothesis that follicles exposed to high levels of FSH during ovarian stimulation will respond with an inappropriately high LHR expression. This in turn causes a high P4 output in response to the trigger. This study further expands our understanding of the underlying mechanisms affecting reproductive outcomes in relation to ovarian stimulation. STUDY FUNDING/COMPETING INTEREST(S): The authors received no specific funding for this work and disclose no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.